"What Motivates You Doesn't Motivate Me": Individual Differences in the Needs Satisfaction–Motivation Relationship of Romanian Volunteers. Issue 2 (5th October 2012) - Haivas, Simona; Hofmans, Joeri; Pepermans, Roland
<x xml:space="preserve">Abstract</x> The present study examines individual differences in the relationship between two core concepts of the self‐determination theory (SDT), namely satisfaction with the autonomy, competence, and relatedness need and motivation (autonomous vs. controlled). Based on the values component of SDT we hypothesised at least two different subpopulations with different need satisfaction–motivation patterns. Data from 349 Romanian volunteers revealed that two groups (or subpopulations) of volunteers can be distinguished, supporting our hypothesis. For the first and largest group, the pattern is in line with the SDT assumption that satisfaction of the autonomy and competence need has an effect on the autonomous forms of motivation. This group is in line with people endorsing intrinsic values. The second group of volunteers, however, revealed that satisfaction with the relatedness need links up with the controlled forms of motivation, and satisfaction of autonomy and competence needs does not predict autonomous motivation. This group is expected to favor extrinsic values. Both relationship patterns were further linked to work engagement and intention to quit, in order to shed light on the practical importance of the observed differences.